Does Preeclampsia Predict the Risk of Late Postpartum Eclampsia? - Wolfe, Diana S. (Thieme Medical Publishers, 2013)
Objective To investigate potential predictive symptoms of late postpartum eclampsia (LPE). Study Design Retrospective review of patients delivered at a single academic medical center and diagnosed with eclampsia greater than 48 hours postdelivery. Results Among 19 patients with eclampsia, 5 (26%) patients with confirmed eclampsia seized greater than 48 hours after delivery. None of these patients showed evidence of preeclampsia intrapartum or immediately postpartum and none received intrapartum magnesium sulfate. Prior to seizure activity, 4 of 5 (80%) patients had increased blood pressure and 2 of 5 (40%) had central nervous system symptoms (headache and visual changes). Conclusion Gestational hypertension (GHTN) may be a risk factor for LPE. Consideration of seizure prophylaxis for patients with GHTN may facilitate the prevention of LPE.